Quantitative Structural Activity Relationship Studies On Some Amino Acid Analogues Of Phthilimido Derivatives As Anticancer Agents - R. SRINIVASAN; C.UMA MAHESWARA REDDY; B.JAYAKAR (International Journal of Pharma and Bio Sciences, 2011)
After glucose, amino acids like glutamine, methonine, glycine, alanine, phenyl alanine are a major metabolite necessary synthesizing for the cancer cell. In the synthesis of DNA and RNA, major portions of nitrogen atoms are supplied by amino acids. Structural variants of amino acids may antagonize enzymes involved in DNA and RNA synthesis. A QSAR (quantitative structure–activity relationships) study was performed on some previously synthesized amino acid analogues in order to get insight in the substitution requirements for their anticancer activity as well as to overcome the symmetry restriction of De Novo model and time consuming determination of partition coefficients of Hansch analysis. A good QSAR model was obtained considering anticancer activity, i.e., log % of tumor weight inhibition which expresses the biological activity, of three phthilimido derivatives which is a analogues of amino acid as dependent variable and substitution contribution at specific position as independent variable as evidenced by the statistical data (r = 0.8122, s = 0.1196, F = 1.3755).